A Qualitative Study on Engaged Families' Experiences with Long-Term Follow-Up Care in the Colorado/Wyoming Newborn Screening System - Stacey Quesada; Lauren Barringer; Marci K. Sontag; Yvonne Kellar-Guenther (MDPI AG, 2024)
Understanding whether the long-term follow-up (LTFU) system is working for families is critical to measuring the success of newborn screening (NBS) and understanding why some families are lost to follow-up. Caregivers were recruited from six pediatric specialty care clinics. Data were gathered from caregivers via five focus groups and one individual interview (n = 24). Caregiver participants represented a wide range of children's ages and conditions identified through NBS. While this is not the first study to gather caregivers' input on LTFU, it provides a wide breadth of perspectives (e.g., metabolic, endocrine, hemoglobinopathy, etc.). When asked about goals for their children, caregivers identified health-related goals (i.e., children able to care for themselves, not hindered by diagnosis) and non-health related goals (i.e., defining themselves outside of disease, participating in sports, making friends). In describing the LTFU care they want and need for their child and the key factors that influence access and engagement, caregivers identified three themes: communication and relationships with providers; care team roles and factors; and care access and utilization factors. The themes identified are not disjointed; they are intertwined and illustrate the lived experiences of a sample of families engaged in LTFU care.